2016
DOI: 10.1590/1982-021620161832516
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação clínica da língua em adultos jovens

Abstract: Purpose: to verify the relationship between the aspects of tongue clinical evaluation. Methods: a cross-sectional study was conducted with 48 healthy adults, 13 men and 35 women (ages 20-44 years, M=24.8 years, SD=5.3years). The following aspects were checked: tongue force, alternate movements, snap, suctionand vibration of the tongue. The evaluator also checked ifthe floor of the mouth elevated during tasks of tongue elevation or sucking tongue on palateand the occurrence of lingual tremor. Results: the aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 15 publications
1
20
1
6
Order By: Relevance
“…However, association between the tongue aspects obtained in qualitative clinical assessment is still little studied. A previous study (15) investigated the association between the aspects of tongue clinical evaluation in healthy young adults and verified that the level of force influences lingual praxis performance. The authors also observed that changes in the vibration task tended to be accompanied by other difficulties, such as in tongue snap and elevation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, association between the tongue aspects obtained in qualitative clinical assessment is still little studied. A previous study (15) investigated the association between the aspects of tongue clinical evaluation in healthy young adults and verified that the level of force influences lingual praxis performance. The authors also observed that changes in the vibration task tended to be accompanied by other difficulties, such as in tongue snap and elevation.…”
Section: Introductionmentioning
confidence: 95%
“…In the mobility assessment, participants were requested to perform movements of snapping the apex and body of the tongue, sucking the tongue on hard palate, sucking the tongue on hard palate for 5s, and vibrating it (15) ; the model was provided by the examiners. Each of these tasks was classified as normal, altered, or absent.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Os fones que se alteram são: o fl ape alveolar, os grupos consonantais compostos com "r" e/ou "l" e as fricativas alveolares "s" e "z". A língua é um aglomerado de músculos que se dividem em duas categorias: extrínsecos e intrínsecos 9,10,11,12 . Devido a essa complexa constituição de fi bras musculares, ela tem a capacidade de mudar sua forma e posição de maneira rápida e complexa 11 .…”
Section: Odokuma Ei Et Al 2008unclassified
“…A língua é um aglomerado de músculos que se dividem em duas categorias: extrínsecos e intrínsecos 9,10,11,12 . Devido a essa complexa constituição de fi bras musculares, ela tem a capacidade de mudar sua forma e posição de maneira rápida e complexa 11 . Também fora demonstrado que 54% da língua é constituída por fi bras de contração lenta 12 .…”
Section: Odokuma Ei Et Al 2008unclassified
“…Os dados categóricos foram representados por frequência absoluta Isso irá implicar na deglutição como um todo, como pode ser visto pelos trabalhos de Logemann, 25 Logemann e Bytell, 26 Pauloski et al 85 , Sanders e Mu 86 , Pauloski et al 87 e Rezende et al 88 Bressmann et al 89 No material de estudo, apenas um paciente fez radioterapia prévia, o que poderia contribuir para aumentar o índice de necroses parciais ou totais, como chamaram a atenção Magrin et al 33 As necroses parciais e totais tiveram uma incidência menor nos casos de tumores de orofaringe -quatro (2,2%) e duas (1,1%), respectivamente; nos casos de tumores de hipofaringe, não ocorreram necroses parciais e houve apenas um caso (0,5%) de necrose total. Nessa situação, o pedículo do retalho se acomoda numa posição mais anatômica e fisiológica sem rotação acentuada para a orofaringe e sem qualquer torção para a reconstrução da hipofaringe, o que irá facilitar a nutrição e a drenagem venosa do retalho, sendo então menos frequentes as necroses nesses casos.…”
Section: Análise Estatísticaunclassified